Non-isothermal crystallization kinetics of partially miscible ethylene-vinyl acetate copolymer/low density polyethylene blends (eXPRESS Polymer Letters)
The non-isothermal crystallization kinetics of ethylene-vinyl acetate copolymer (EVA, 14 wt% vinyl acetate content), low density polyethylene (LDPE) and their binary blends with different blending ratio were investigated via differential scanning calorimetry. Jeziorny theory and Mo’s method were utilized in evaluating the crystallization behavior of both neat materials successfully. In the primary crystallization stage both EVA and LDPE had three-dimensional spherulitic growth mechanism. Apparently the crystallization rate of LDPE was faster than that of EVA at a low cooling rate. Increase in cooling rate limited the spherulites’ growth, which narrowed their rate difference. Influences from blending on the crystallization kinetics of each component in EVA/LDPE mixture were evaluated by Kissinger’s activation energy (∆E) and Khanna’s crystallization rate coefficient (CRC). Inter-molecular interaction in the melt increased the ∆E of both EVA and LDPE components at the beginning of cooling. During the primary crystallization stage of LDPE, dilution effect from EVA facilitated the crystal growth in LDPE. Co-crystallization between EVA component and the secondary crystallization stage of LDPE component also increased the CRC of EVA. In blend of EVA/LDPE = 7/3, LDPE obtained the maximal CRC value of 174.2 h–1. Results obtained from various approaches accorded well with each other, which insured the rationality of conclusion.